The activist collector : Lida Clanton Broner's 1938 journey from Newark to South Africa - Clarke, Christa (Newark Museum of Art ; Rutgers University Press, 2022)
"After twenty-eight years of desire and determination, I have visited Africa, the land of my forefathers." So wrote Lida Clanton Broner (1895-1982), an African American housekeeper and hairstylist from Newark, New Jersey, upon her return from an extraordinary nine-month journey to South Africa in 1939. This epic trip was motivated not only by Broner's sense of ancestral heritage, but also a grassroots resolve to connect the socio-political concerns of African Americans with those of black South Africans under the segregationist policies of the time. During her travels, this woman of modest means circulated among South Africa's black intellectual elite, including many leaders of South Africa's freedom struggle. Her lectures at black schools on "race consciousness and race pride" had a decidedly political bent, even as she was presented as an "American beauty specialist." How did Broner--a working class mother--come to be a globally connected activist? What were her experiences as an African American woman in segregated South Africa and how did she further her work after her return? Broner's remarkable story is the subject of this book, which draws upon a deep visual and document-ary record now held in the collection of the Newark Museum. This extraordinary archive includes more than 150 objects, ranging from beadwork and pottery to mission school crafts, acquired by Broner in South Africa, along with her diary, correspondence, scrapbooks, and hundreds of photographs with handwritten notations.